CERVICAL HIBERNOMA : TWO CASE REPORT AND LITERATURE REVIEW - Yassir HIOUKANE (Faculté de Médecine et de Pharmacie, Rabat - Thèse de médecine, 2022)
Introduction : The hibernoma is a rare, benign adipocytic tumor of the soft tissues. Believed to grow at the expense of embryonic remnants of brown fat. Modern imaging takes an important place in the diagnosis approach. Histological examination confirms the benign nature of the lesion and eliminates liposarcoma. The aim of our work was to review hibernomas, their epidemiological, clinical, diagnostic and therapeutic characteristics through 2 clinical cases and a review of the literature. Material and methods : We present two cases of giant cervical hibernoma observed at the Military Hospital Mohammed V of Rabat's Thoracic Surgery Department. Treated surgically, without recurrence or malignant transformation. Results : Two patients, aged respectively 58 and 60 years, male, presented with an enormous cervicothoracic mass of average size 144 mm. The cervico-thoracic CT scan showed a tissue mass, well circumscribed without loco-regional invasion. Complete surgical resection was performed in both cases, and histological examination confirmed the diagnosis of hibernoma. After 2 years, no recurrence was observed. Conclusion : Hibernoma is a rare benign tumor that can mimic malignant lesion of the soft tissue such as liposarcoma. MRI is still limited for the differential diagnosis of malignancy, it plays a critical role in the differential diagnosis, particularly with other benign tumors. Surgery corresponds to the gold standard approach for the final diagnosis and treatment
Keywords: Cervical mass; Hibernoma; MRI; Surgery